Informal elections with dispersed information: Protests, petitions, and nonbinding voting - Mehmet Ekmekci; Stephan Lauermann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We study information transmission through informal elections. Our leading example is that of protests in which there may be positive costs or benefits of participation. The aggregate turnout provides information to a policy maker. However, the presence of activists adds noise to the turnout. The interplay between noise and participation costs leads to strategic substitution and complementarity effects in citizens' participation choices, and we characterize the implications for the informativeness of protests. In particular, we show that rather than being a friction, costs may facilitate information transmission by lending credibility to protest participation.
Keywords: D72; 330; Political; Institutions